Functional Characterisation of Eel Dopamine D2 Receptors and Involvement in the Direct Inhibition of Pituitary Gonadotrophins. (15th September 2016) - Jolly, C.; Rousseau, K.; Prézeau, L.; Vol, C.; Tomkiewicz, J.; Dufour, S.; Pasqualini, C.
Abstract : In various vertebrate species, dopamine (DA) exerts an inhibitory action on reproduction. In the European eel, DA plays a pivotal role in the inhibitory control of gonadotroph function and the blockade of puberty. In vivo studies have suggested that this effect is mediated by receptors pharmacologically related to the D2 family. In the European eel, two distinct D2 receptor (D2‐R) paralogous genes have been identified (D2A‐R and D2B‐R) and both were shown to be expressed in the pituitary. We investigated the potential role of each paralogue in the control of gonadotroph function in this species. Eel recombinant D2A‐R or D2B‐R were expressed in HEK 293 cells, with a universal Gα subunit, and receptor activation was followed by inositol phosphate production. Recombinant D2‐Rs exhibited a comparable affinity for DA, although they had differential affinities for mammalian D2‐R agonists and antagonists, supporting subtle structure/activity differences. Furthermore, using eel pituitary cell primary cultures, the expression by gonadotroph cells of both native eel D2‐R paralogues was examined by in situ hybridisation of D2A‐R or D2B‐R transcripts, coupled with immunofluorescence of luteinising hormone (LH)β or follicle‐stimulating (FSH)β. LH and to a lesser extent, FSH cells expressed both D2‐R transcripts but with a clear predominance of D2B‐R. Notably, D2B‐R transcripts were detected for the majority of LH cells. Accordingly, using these cultures, we showed that DA potently inhibited basal and testosterone‐stimulated LHβ expression and less potently basal and activin‐stimulated FSHβ expression. We also tested some D2‐R antagonists, aiming to select the most adequate one to be used in innovative protocols for induction of eel sexual maturation. We identified eticlopride as the most potent inhibitor of DA action on basal and stimulated LH expression in vitro . Our data suggest a differential functionalisation of the duplicated receptor genes and demonstrate that mainly D2B‐R is involved in the dopaminergic inhibitory control of eel gonadotroph function.